KEABSAHAN PEMBATALAN HIBAH AKIBAT PEMBERI HIBAH JATUH MISKIN - Adhani, Oktaviana; Atmaja, Bagiyo (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2020)
A grant is a gift that starts in effect since it is implemented. not infrequently the grant as a voluntary gift raises problems that occur because there are other parties who raise objections to the grant. This study analyzes the validity of grants to minors represented by their mothers and the legal position of cancellation of grants due to poor grants. The research method used is normative juridical by using the statutory approach and conceptual approach. The results of the study showed that the grants for the inheritance of the giver of grants to minors and received by their mothers were legal. The provisions in the Civil Code govern that grants can be revoked and canceled The word